Pemanfaatan Content Management Sistem Dengan Metode Waterfall Untuk Membuat Official Site Wilayah Keanggotaan Pada Asosiasi - Rahardja, Untung; Harahap, Eka Purnama; Darmawan, Muhammad Diky (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
Each association or organization must have an official site that is useful to provide accurate information about the organization to its members and the wider community. Official site is used as a medium of information, communication media and educational media for its members, students and the wider community. However, the current membership area of the Association of Indonesian Private Universities (APTISI), amounting to 13 regions has not had official official site so that the delivery of information is still using the manual way. In this case the official site APTISI Pusat can become the main website to make official membership site by using sub directory. In this research, using descriptive research method. Supported by technique 3 (three) data collecting technique that is observation, literature study and impelementasi. In the system development stage using waterfall method which is one of the method of SDLC (Systems Development Life Cycle). The alternative problem solving is the official site of the Association of Indonesian Private Universities (APTISI), an official site used as a container / place and media information that is devoted to its members and can display and improve the performance of association activities